Experimental complex for research of vibration protection combined system of transportation and technological machines operator - Y. A. Buriyan; V. N. Sorokin; N. V. Zakharenkov; A. F. Zelov (Вестник СибАДИ)
The article is devoted to the structure and description development of the technical solutions which used in the stand design for studying the dynamics of the transport and technological machines operator vibration protection combined system which used in building. As a load-bearing elements of passive and active vibration protection systems are encouraged to use rubber-cord casing. Stand structure should allow to evaluate the contribution of both passive and active vibration protection system in the general process of oscillations suppression.